Risk Management as a Moderator of the Influence of Good Corporate Governance on Corporate Sustainability in Village Credit Institutions - MAHARANI, Ida Ayu Dinda Priyanka; PURBA, Ida Bagus Gde Indra Wedhana (PT Keberlanjutan Strategis Indonesia, 2024)
Village Credit Institutions (hereinafter referred to as LPD) in Bali were established based on Bali Regional Regulation Number 2 of 2002 and have been amended several times. The existence of LPD is needed to ensure the realization of the welfare of the traditional village community. LPD must continue to strive so that its sustainability is maintained properly. A number of LPDs in Bali have developed well and their benefits are felt by the village community, but there are also LPDs in a number of villages that have not been able to develop well, and some are even not operating. Based on these conditions, this study was conducted to analyze a number of factors that can affect the sustainability of LPDs in Bali. This study focuses on those that are most likely to affect the sustainability of LPDs, This study focuses on good corporate governance and credit risk management in LPDs in Gianyar Regency. Good corporate governance includes six dimensions: participation, responsibility, independence, fairness, accountability, and transparency. Corporate sustainability is assessed through economic, social, and environmental performance. The research sampled 84 healthy LPDs registered with the Village Credit Institution Empowerment Institution (LPLPD) using purposive sampling. The LPD chairpersons served as respondents, and data analysis was conducted using the structural equation modeling (SEM) method based on partial least squares (PLS).